Bismuth-catalyzed allylic oxidation using t-butyl hydroperoxide - Salvador, Jorge A. R. (2005)
Bismuth(III) salts are efficient catalysts for the selective allylic oxidation using tert-butyl hydroperoxide. BiCl3 is especially effective and can be easily recovered and reused as BiOCl. Using BiCl3/K-10 as catalyst, an increase in the reaction rate was observed.